China and the affirmation of African economic sovereignty - (:unkn) unknown (My University, 2025)
Economic sovereignty refers to a state's ability to govern its economy autonomously. If, as François Perroux observed, 'the centres of industrial production are economic areas that do not coincide with the geographical areas over which the power of a national state is exercised', then it is clear that this economic sovereignty is increasingly under threat, particularly for the benefit of the least developed countries, who are the victims of 'structural imperialism' by multinational companies based in major powers. Fifteen years after François Perroux's observation, Raymond Vernon published the results of a Harvard research programme in what has become a classic study, denouncing the 'sovereignty at risk' of developing countries hosting American multinationals. At the time, neither the French nor the American economist could think of China, even though Perroux was referring specifically to the USSR alongside the United States. In light of this, it is pertinent to consider whether Chinese companies operating in Africa today could potentially undermine the economic sovereignty of African countries in a similar manner to their French, British and other predecessors.This study will shed light on the interference of Chinese players, which is no more or less systematic or absolute than that of other players. Indeed, as will be demonstrated, African countries, through their own strategies, are able to demonstrate their agency, despite their limited margins for manoeuvre.
Keywords: African Research